Health Care Fraud and Abuse: Lessons From One of the Largest Scandals of the 21st Century in the Field of Spine Surgery - Thomas Szewczyk, BS; Michael S. Sinha, MD, JD, MPH; Jack Gerling, BS; Justin K. Zhang, MD, MSCI; Philippe Mercier, MD, PhD; Tobias A. Mattei, MD, FACS (Annals of Surgery Open)
Up to hundreds of billions of dollars are annually lost to fraud and abuse in the US health care, making it a significant burden on the system. This study investigates a specific instance of health care fraud in spine surgery, in which a medical device company ended up paying $75 million to settle violations of the False Claims Act. We review the surgical background regarding the kyphoplasty procedure, as well as its billing and reimbursement details. We also explore the official legal complaint brought by the US Department of Justice to tell the story of how one of the most significant medical innovations in spine surgery in the 21st century turned into a widespread fraudulent marketing scheme. In the sequence, we provide a detailed root cause analysis of this scandal and propose some proactive measures that can be taken to avoid such type of unfortunate events. Ultimately, this historical health care scandal constitutes a valuable lesson to surgeons, health care administrators, medical device companies, and policymakers on how misaligned incentives and subsequent unscrupulous practices can transform a medical innovation into an unfortunate tale of fraud and deceit.